The Construction of Academic Fiqh in the Faculty of Shariah in Disruption Era - Muchsin, Agus (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2023)
World progress has been increasingly visible in the last three years, namely during the outbreak of the Covid-19 pandemic with the impression of destroying social activities (af'al al mukallafin) between individuals with each other, thus triggering the birth of a new community culture as a form of response to the policy of limiting social activities. This assumption is very relevant to the etymological definition of fikhi as al fahmu (understanding) or al sains bi syain (knowledge of something), in its pathosophical framework chart, that understanding will rest on nisby (relative) truth. The writing method uses qualitative with library research companions as support. The results of the study said that the development of science and technology has an influence on the progress of civilization from social and religious aspects such as in the fields of economics, culture, politics and law so that the construction of academic Fikhi theoretically paradigms through the concept of dialectics.